ANALYSIS OF LEXICAL AND SEMANTIC TRANSFORMATIONS IN POETRY TRANSLATION (Journal of Universal Science Research, 2023)
This article analyzes the lexical and semantic transformations used in the process of poetic translation, one of the most common types of translation among young people who love literary literature today.  In addition, the article examines how poems are translated from one language to another and what methods are used to translate them.  Various manuals and a collection of translated poems are taken as a source for the article.